Edukasi Masyarakat Umum Seputar Covid-19 Di Masa Pandemi Guna Mencegah Penularan - Yeni Agustin (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Coronavirus Disease 2019 (Covid-19) is a disease caused by the corona virus. The corona virus is a new type of virus that started attacking in 2019 and has never previously been identified to attack humans. During the Covid-19 pandemic, it caused changes in the order of life in carrying out the wheels of daily life. Humans are entering the new normal era, an era where we adapt to new habits. Our cohesiveness and compliance are indispensable in implementing health protocols during daily activities as a preventive measure. Behavior change is key in handling the Covid-19 pandemic. Changes that require each individual to apply the 3M health protocol (wearing a mask, keeping a distance and avoiding crowds, and washing hands with soap) as a daily habit. The community must also be able to adapt to health protocol regulations when carrying out activities, especially in public spaces. This health protocol arrangement is intended to protect the public, so that all activities can run with the lowest possible risk of transmission.